Anatomical and Functional Consequences of Microneedle Perforation of Round Window Membrane. Issue 2 (February 2020) - Yu, Michelle; Arteaga, Daniel N.; Aksit, Aykut; Chiang, Harry; Olson, Elizabeth S.; Kysar, Jeffrey W.; Lalwani, Anil K.
Abstract : Hypothesis: Microneedles can create microperforations in the round window membrane (RWM) without causing anatomic or physiologic damage. Background: Reliable delivery of agents into the inner ear for therapeutic and diagnostic purposes remains a challenge. Our novel approach employs microneedles to facilitate intracochlear access via the RWM. This study investigates the anatomical and functional consequences of microneedle perforations in guinea pig RWMs in vivo. Methods: Single three-dimensional-printed, 100 μm diameter microneedles were used to perforate the guinea pig RWM via the postauricular sulcus. Hearing was assessed both before and after microneedle perforation using compound action potential and distortion product otoacoustic emissions. Confocal microscopy was used ex vivo to examine harvested RWMs, measuring the size, shape, and location of perforations and documenting healing at 0 hours (n = 7), 24 hours (n = 6), 48 hours (n = 6), and 1 week (n = 6). Results: Microneedles create precise and accurate perforations measuring 93.1 ± 29.0 μm by 34.5 ± 16.8 μm and produce a high-frequency threshold shift that disappears after 24 hours. Examination of perforations over time demonstrates healing progression over 24 to 48 hours and complete perforation closure by 1 week. Conclusion: Microneedles can create a temporary microperforation in the RWM without causing significant anatomic or physiologic dysfunction. Microneedles have the potential to mediate safe and effective intracochlear access for diagnosis and treatment of inner ear disease.